Measurements of hot combustor turbulence spectra - Moss, R; Oldfield, M (American Society of Mechanical Engineers, 1991)
This paper presents measurements of turbulence spectra at the exit plane of aircraft turbine combustors running at atmospheric exit pressure. These measurements are important in providing realistic input conditions for both experimental measurements and CFD predictions of first stage turbine heat transfer.A transient technique in which a pitot probe was only briefly exposed to the flow allowed uncooled, flush mounted sub-miniature pressure transducers to be used for measuring the turbulence spectra of combustor exhaust gases at temperatures up to 1500K. Three different burner configurations were tested at fuel:air ratios from 0 to 0.02. It was found that the combustion process makes little difference to the turbulence power spectrum at wavenumbers between 100 and 1200 m-1. The effect of using two fuels with different burning rates (paraffin and diesel) was also studied.A brief description of the probe calibration is included. The response was found to be a function of both frequency and wavenumber.